2017
DOI: 10.1016/j.brat.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Perseverate or decenter? Differential effects of metacognition on the relationship between parasympathetic inflexibility and symptoms of depression in a multi-wave study

Abstract: Depression often is characterized by inflexible autonomic and metacognitive processes that interfere with effective self-regulation. However, few studies have integrated these factors to improve the prediction of which individuals are at greatest risk for depression. Among 134 undergraduates, we evaluated whether parasympathetic inflexibility (a lack of reduction in respiratory sinus arrhythmia) in response to a sadness induction involving loss would prospectively predict symptoms of depression across four wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 109 publications
(145 reference statements)
2
11
0
Order By: Relevance
“…However, resting vmHRV has been recently described as an endophenotype (including for anxiety disorders), thus supporting our current conceptualization as an independent variable (for review, see Thayer and Lane, 2009 ). A recent study lends further evidence in this regard, as it displayed a relationship between parasympathetic inflexibility (i.e., resting-to-reactive vmHRV) and prospective symptoms of depression was exacerbated by perseverative cognition (Stange et al, 2017 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, resting vmHRV has been recently described as an endophenotype (including for anxiety disorders), thus supporting our current conceptualization as an independent variable (for review, see Thayer and Lane, 2009 ). A recent study lends further evidence in this regard, as it displayed a relationship between parasympathetic inflexibility (i.e., resting-to-reactive vmHRV) and prospective symptoms of depression was exacerbated by perseverative cognition (Stange et al, 2017 ).…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, we previously reported that perseverative cognition is an important mechanism linking stress vulnerability (e.g., lower resting vmHRV) with psychological outcomes such as anxiety (for review, see Brosschot et al, 2010 ; Verkuil et al, 2010 ) and depression (Stange et al, 2017 ). A longitudinal report provides evidence in support of this idea, showing that perseveration, specifically rumination, was a significant mediator linking stressful events with both anxiety and depression over the lifespan (Michl et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we have decided to leave these factors in a separate category (because their categorization may not be as immediately clear-cut as others), and these factors include: low-level light [ 429 ], weight cycling [ 430 ], water contaminants [ 431 ], trade [ 432 ], air pollution [ 433 , 434 ], program-level variables (ex. feedback and learning experience) [ 435 ], TV viewing [ 436 ], falls [ 437 ], various other biological factors [ 116 , 136 , 141 , 151 , 164 , 182 , 363 , 364 , 438 , 439 , 440 , 441 , 442 , 443 , 444 , 445 , 446 , 447 , 448 , 449 , 450 , 451 , 452 , 453 , 454 , 455 , 456 , 457 , 458 , 459 , 460 , 461 , 462 , 463 , 464 , 465 , 466 , 467 , 468 , …”
Section: Resultsmentioning
confidence: 99%
“…Further work is needed on this and the underpinning mechanisms between the determinants and outcomes. This review highlighted the myriad ways of measuring depression and its determinants [ 66 , 85 , 281 , 298 , 451 , 485 ]. Thus, the standardization of the measurements of the outcomes (ex.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although self-report is not sufficient for a comprehensive assessment of affective processes and internalizing symptoms, it does provide necessary and critical information. Whenever possible, self-report measures should be used in conjunction with other levels of analysis (e.g., genes, psychophysiology, neurological circuits, cognitive measures, behavioral outcomes) to combine complementary sources of information and yield a more complete picture of affective experience (see, for example, Stange et al, 2017; Tull et al, 2018). It is also important to use psychometrically-sound self-report measures that were thoughtfully selected for the specific research question at hand.…”
Section: Measurement Challenges and Recommendationsmentioning
confidence: 99%